Antidiabetic constituents of Dendrobium officinale as determined by high-resolution profiling of radical scavenging and α-glucosidase and α-amylase inhibition combined with HPLC-PDA-HRMS-SPE-NMR analysis. (June 2019) - Chu, Chu; Li, Tuo; Pedersen, Hans Albert; Kongstad, Kenneth T.; Yan, Jizhong; Staerk, Dan
Graphical abstract: Highlights: Two new and eight previously described bibenzyls were isolated from Dendrobium officinale . Triple high-resolution radical scavenging/α-glucosidase/α-amylase profiling combined with HPLC-PDA-HRMS-SPE-NMR was undertaken. 3, 4-Dihydroxy-4′, 5-dimethoxybibenzyl showed α-glucosidase and α-amylase inhibition as well as radical scavenging activity. Three compounds were reported as α-glucosidase inhibitors and one as α-amylase inhibitor for the first time. Abstract: Type 2 diabetes is a chronic metabolic disorder affecting millions of people worldwide, and new drug leads are urgently needed. The dried stem of Dendrobium officinale is used in China to alleviate the symptoms of diabetes, but investigations of its bioactive components have been limited. We have applied a simple, fast, and effective method, combining triple high-resolution profiling of radical scavenging and α-glucosidase and α-amylase inhibition with high-performance liquid chromatography - photodiode-array detection - high-resolution mass spectrometry - solid-phase extraction - nuclear magnetic resonance spectroscopy (HR-bioassay/HPLC-PDA-HRMS-SPE-NMR). Two new compounds, 3, 4, 4′-trihydroxy-5-methoxybibenzyl (5 ) and 3, 4-dihydroxy-3′, 4′, 5-trimethoxybibenzyl (8a ), along with fourteen known compounds, were identified. Twelve of these were associated with radical scavenging activity, six with α-glucosidase inhibition, and one with α-amylase inhibition. Compound5, dendrocandin U, and 3, 4-dihydroxy-4′, 5-dimethoxybibenzyl (12 ) are reported as α-glucosidase inhibitors for the first time, and12 is furthermore reported as an α-amylase inhibitor for the first time.